Agente comunitário de saúde : processo de trabalho na mediação entre equipe e comunidade - Medeiros, Alba Regina Silva (2020)
This thesis deals with the result of research on the health work process of the Community Health Agent (CHA) inserted in the Family Health Strategy (FHS) teams of the Primary Health Care System of the Unified Health System, in the city of Cuiabá / MT- Brazil. CHA have an important role in building bonding and accountability, promoting mediation between staff and community and carrying out their activities on the streets and inside homes, in constant displacement, but in a very peculiar way, as, as they provide services, they are at the same time residents in their own territory. The objective was to understand the work process in direct interaction with the population and its singularities, developed by Community Health Agents, linked to the family health strategy teams. This research had as structuring concepts the Work, Worker's Health, Process, Organization, Working Conditions and Services Sector, with support in the Marxist theory and in the light of the psychopathology of the work of Christophe Dejours with the approach of pleasure and suffering in the singularity of the situations faced by health workers. The assumption of the study is that, in carrying out the work, the CHA develop different practices and interactions with the community and the team, which reflect the context of the social situation of the residents and extrapolate the prescribed work, reflecting on their lives and, thus outlining, the form of health intervention in the territory in which the agents operate. The study had 49 participants in total and the approach was qualitative, using the techniques of Conversation Wheel (49 CHA), Participant Observation (16 CHA) and Interview (eight CHA). At the end of the Round, a structured questionnaire was applied with the forty-nine (49) CHA assigned to the eight Basic Health Units (UBS), two of which were drawn from each regional in Cuiabá - East, West, North and South, in the years 2018 and 2019. As a result, we present two articles that have been approved and are in the process of being published: ARTICLE 1: “Use of virtual social networks to monitor violence at work suffered by community health workers” and ARTICLE 2: “The community health worker and the manifestation of violence at work” and one in the process of construction - ARTICLE 3: “Narratives of the Community Health Agent: about the real work”. The analysis was carried out from the understanding of the observer and the observed - study participants - in the field, through Thematic Analysis based on the structure of Braun and Clarke (2006) in a systematic way to describe and explain the whole process within the context of the search. This form of analysis consists in identifying patterns or themes within qualitative data. The study revealed that the increase in violence in the city has greatly influenced the work of agents; that the Workers' Health Surveillance System does not notify these as arising from work and that many activities are developed according to the commitment of each agent, extrapolating the prescribed activities and these are not incorporated by the ESF teams from the perspective of service-community integration and intersectoral and interinstitutional policies in the field of Health.